PERSEPSI REMAJA BALI TENTANG KEHAMILAN PRANIKAH - Tisnawati, Ni Made; Suasti Wulanyani, Ni Made (PIRAMIDA; Vol. 2, No. 2 Desember 2006, 2012)
This research analyzes the Balinese youth?s perception on pre marital sex and pregnancy. The results of the research were analyzed through a descriptive interpretative approach in order to understand premarital sex and pregnancy. Based on the analysis, the conclusion are: there are communication problems in the family, so that the understanding of sexuality among youth is usually formed by sources outside the family. There?s no relation was found between premarital sex and social economic status of the family. In Bali, premarital pregnancy indicates the constant efforts of young people to challenge the status quo in Bali which places certain castes in a higher position than others. Therefore, the roles of many institution such as: school, government, non-governmental organization, and religious community (PHDI) should be increasing.
Keywords: perception, premarital sex and pregnancy, the youth